Mobilizing Pompeii for Italian Silent Cinema. (17th September 2019) - Wyke, Maria
Abstract: A documentary film about the eruption of Vesuvius in 1906 juxtaposes scenes of the damage and deaths it caused in neighbouring communities with shots of Pompeii — the ancient city of the long-since dead. The documentary suggests that Pompeii is a picturesque site where the privileged tourist experiences aesthetic detachment from the excavators' labour or the locals' suffering. Despite this critique, four Italian fiction films about the last days of Pompeii were made between 1908 and 1926. This article explores those films and argues that they mobilize Pompeii both for modern Italians and for cinema. They situate viewers immersively within the reconstructed city and substitute for a detached tourist gaze an impassioned, participatory one.